1996
DOI: 10.1002/ana.410390215
|View full text |Cite
|
Sign up to set email alerts
|

A placebo‐controlled trial of recombinant human ciliary neurotrophic (rhCNTF) factor in amyotrophic lateral sclerosis

Abstract: Preclinical investigations indicated that recombinant human ciliary neurotrophic factor (rhCNTF) may have potential as therapy for amyotrophic lateral sclerosis (ALS). We evaluated the safety and efficacy of rhCNTF in a prospective, double-blind, placebo-controlled trial in 570 patients with ALS. Patients were randomized to receive 0.5, 2, or 5 micrograms/kg/day rhCNTF, or placebo, for 6 months. The primary efficacy end point was the change from baseline to the last on-treatment value of a combination megascor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
162
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(164 citation statements)
references
References 7 publications
0
162
0
2
Order By: Relevance
“…Brain-derived neurotrophic factor in ALS patients had no effect on survival but exhibited a statistically significant benefit for those ALS patients with early respiratory impairment and altered bowel function (70). Ciliary neurotrophic factor exhibited mostly negative effects in ALS patients (71).…”
Section: Discussionmentioning
confidence: 97%
“…Brain-derived neurotrophic factor in ALS patients had no effect on survival but exhibited a statistically significant benefit for those ALS patients with early respiratory impairment and altered bowel function (70). Ciliary neurotrophic factor exhibited mostly negative effects in ALS patients (71).…”
Section: Discussionmentioning
confidence: 97%
“…50 So far, side effects of CNTF such as fever, malaise, and weight loss as well as the most likely poor ability of CNTF to cross the intact BBB have limited the success of clinical studies in amyotrophic lateral sclerosis patients who were given CNTF because of its known neuroprotective effect. 28,31,32 More promising results were obtained when CNTF was administered to the CNS by intrathecal injections or implantation of encapsulated transfected cells into the ventricular system. 34,36,37,81,82 Recent progress on human CNTF biochemistry indicated that this cytokine can use soluble or membrane-bound IL-6R␣ as a substitute to CNTFR␣ to activate the receptor signaling subunits, gp130 and LIFR␤.…”
Section: Discussionmentioning
confidence: 99%
“…28 -30 CNTF was administered systemically to patients with amyotrophic lateral sclerosis, but no beneficial effect was detected. 28,31,32 The lack of therapeutic efficiency could be linked to the poor ability of CNTF to pass the bloodbrain barrier (BBB). 33 More promising preclinical or clinical results have been obtained with CNTF targeted to the CNS by intrathecal injection or implantation of encapsulated transfected cells.…”
mentioning
confidence: 99%
“…In vitro studies demonstrated that several neurotrophic factors delay motorneuron degeneration [3][4][5][6]. However, clinical trials using subcutaneous and intrathecal neurotrophic factors caused several side effects such as weight loss, fever, cough, fatigue and behavioural changes [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%